Peran Penting Metode Takhrij dalam Studi Kehujjahan Hadis - Arif Maulana (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to discuss the important role of the takhrij hadith method in the study of the authenticity of the hadith. This research method uses a qualitative approach with an analytical descriptive method, namely a fact-finding method with proper description and analysis of the data studied, including a general understanding of takhrij hadith, various methods of takhrij hadith, as well as the purpose and benefits of takhrij hadith. From this research, it can be concluded that takhrij hadith is the result of the efforts of previous scholars in developing the study of hadith science which is also part of the intellectual and scientific treasures that must be passed on by subsequent generations so that it continues to be maintained and developed. This research is expected to provide benefits and benefits for the treasures of Islamic scholarship.